A web-page-based software program for technology-enhanced learning (TEL) of Karnaugh map (K-map) - Chua, Alex Jun Kiat (Nanyang Technological University, 2024)
Karnaugh Map (K-map) is a tool to visually simplify Boolean expressions. Learning K-map is an important part of electronics and computer engineering education. This report documents the implementation of a program that enhances the learning of K-maps. The objective is to create an easily accessible website that allow students to explore K-maps in an interactive manner, using Technology-Enhanced Learning (TEL) to strengthen and reinforce logic minimization techniques for students.